Analisis Deskriptif Komponen Pertumbuhan Ekonomi Wilayah dalam Mendorong Pembangunan Sektor Pertanian dan Perekonomian Perdesaan Kabupaten Probolinggo - Junaedi, Deddy; Nafi’ah, Alisa Hidayatun; Wulandari, Ayu Widia; Aisyah, Dita; Lutfiana, Evi; Fitriyah, Lailatul; Rohmah, Siti Nurul (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study aims to analyze the components of economic growth in Probolinggo Regency in order to support agricultural development and the rural economy. The study uses a quantitative descriptive method with secondary data from the Probolinggo Regency Central Statistics Agency (BPS) and local government documents for the 2022–2025 period. The analysis focuses on the development of the Gross Regional Domestic Product (GRDP), the regional economic structure, the contribution of the agricultural sector to the GRDP and employment, as well as the dynamics of livelihood diversification in rural areas. The results show that the economy of Probolinggo Regency is still dominated by the agriculture, forestry, and fisheries sectors, which contribute the most to GRDP and employment, with a positive but vulnerable economic growth trend due to dependence on primary commodities and infrastructure limitations. Agricultural productivity has increased for several horticultural and food commodities, but challenges such as price fluctuations, climate change, and limitations in irrigation and market access still hinder the optimization of economic benefits. The findings also emphasize the strategic role of strengthening local institutions such as BUMDes and developing MSMEs in increasing the added value of agricultural products. Policy recommendations emphasize the need for investment in agricultural infrastructure, strengthening technical and marketing services, and economic diversification strategies to create inclusive and sustainable growth.